(3aJM GdPNGFQ hGdCZdGb aj TQM JQLeGf GdCThGbs - (3eMeO Hf Ydj Hf eMeO Hf YQHj , CHh HcQ GdMGJej GdWGFj GdCfOdSj, GdeYQha HeMjj GdOjf GHf YQHj,J (B638 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdMSf GdaYGd GdLejd GdPi jMH GdLeGd CeG HYO aEfi deG fRdJ ecI SfI KeGf hJSYjf hNeSeGFI CdajJ HgG LeGYI ef GdaVdGA s
(3BNQgG (B:s
(3haGM GdeSc hGdLGOi Ci GdPhGJ GdWjHI GdQjM CfeG JcSH GdWjH ef QjMgG GdWjH faMJgG hGddg JYGdi CYde Je GdTQM GdeHGQc s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B281s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B396s
(3eUOQ GbJfGA GdCUd (B:s
(3ShQjG (B(9235) s
Keywords: (3GdCOHs